The identities and social roles of people with intellectual disabilities: Challenging dominant cultural worldviews, values and mythologies - Povee, Kate (Curtin University, 2014)
The aim of this research was to explore the social construction of intellectual disability and to increase the power of people with intellectual disabilities in the research process. Informed by a contextualist perspective, this research was conducted within a participatory framework. Causal layered analysis was used to deconstruct the data revealing a complex dynamic of worldviews and mythologies which served to dehumanise people with intellectual disabilities and blame them for their own fate (victim blaming).